Risk Assessment of Etanercept in Mice Chronically Infected With Toxoplasma gondii - Yang, Jing; Wang, Luyao; Xu, Dongmei; Tang, Ding; Li, Senyang; Du, Fen; Wang, Lixia; Zhao, Junlong; Fang, Rui (Frontiers in Microbiology, 2018)
Toxoplasma gondii (T. gondii) is a zoonotic parasite that severely harms the health of the host. The cysts of T. gondii can reactivate from bradyzoites to tachyzoites, if the individual develops low or defective immunity, causing lethal toxoplasmosis. The host resists T. gondii infection by mediating Th1-type cellular immunity to generate pro-inflammatory cytokines. Tumor necrosis factor (TNF) is an important pro-inflammatory cytokine, which can induce lysosomal fusion of parasitophorous vacuole to kill parasites. Etanercept is a soluble TNF receptor fusion protein, which is widely used clinically to cure autoimmune diseases. The effects and specific molecular mechanisms of etanercept treatment on patients co-infected with autoimmune diseases and chronic toxoplasmosis are rarely reported. In our study, a mouse model of chronic infection with T. gondii and murine macrophages RAW264.7 cells infected with T. gondii were employed to investigate the impact of etanercept on the status of chronic infection. The cytokines levels and a series of phenotypic experiments in vivo and in vitro were measured. In the present study, the expression levels of TNF, IL-1β and IL-6 were decreased and the brain cysts number was increased in mice chronically infected with T. gondii after being treated with etanercept. In vivo experiments confirmed that etanercept caused a decrease in the immune levels of the mice and activated the brain cysts, which would lead to conversion from chronic infection to acute infection, causing severe clinical and pathological symptoms. Murine macrophages RAW264.7 cells were pretreated with etanercept, and then infected with T. gondii. In vitro experiments, the expression levels of cytokines were decreased, indicating that etanercept could also reduce the cells’ immunity and promote the transformation of bradyzoites to tachyzoites, but did not affect the intracellular replication of tachyzoites. In summary, etanercept treatment could activate the conversion of bradyzoites to tachyzoites through reducing host immunity in vivo and in vitro. The results obtained from this study suggest that the use of etanercept in patients co-infected with autoimmune diseases and chronic toxoplasmosis may lead to the risk of activation of chronic infection, resulting in severe acute toxoplasmosis.